KEKUATAN HUKUM PENETAPAN SEMENTARA PENGADILAN (INJUNCTION) SEBAGAI BENTUK PERLINDUNGAN TERHADAP PEMILIK MEREK DARI ADANYA PELANGGARAN MEREK - Inge Dwisvimiar (Jurnal Dinamika Hukum, 2014)
This paper tries to investigate and describe the injunction granted protection in the effort of protecting the trademark owners to avoid greater and wider losses. This is a normative empirical legal research which takes place in Jakarta and Tangerang Regency. The data comprise primary and secondary data by applying qualitative analysis approach done by interactive data collection. The results shows that the concept of injunction has already existed in the PERMA No. 5 Year 2012 on the injunction. Nevertheless, the legal force on injunction is not effectively implemented since PERMA No. 5 Year 2012 is only one and a half year stipulated.The forms of policies that may be made in reforming law are by providing a distinct formulation of injunction elements as well as providing definite boundaries for the Supreme Court in making decision of the court or, if it is possible, it is suggested to establish a kind of procedural law on injunction in the court to accommodate other types of trademark infringements. Key words: injunction, legal strength, trademark infringements